Revitalizing Value Creation of Siaya’s Cotton Sector “Enhancing Productivity, Market Access, and Value Addition” - Jalango, Dorcas Anyango; Okari Caleb; Nguvi, Caroline (2025)
This investment brief was developed under the AICCRA project to guide Siaya County’s investment decisions for revitalizing its cotton sector. The cotton value chain, identified as a priority under the World Bank-funded National Agricultural Value Chain Development Project (NAVCDP) implemented by the Ministry of Agriculture and Livestock Development, seeks to strengthen productivity, enhance community-led extension, and improve water management and data-driven value chain services. The brief outlines strategic investment opportunities that build on these existing interventions to support smallholder farmers’ transition from subsistence to market-oriented commercial production, promoting inclusive growth, climate resilience, and value addition within Siaya County’s cotton industry.